1974
DOI: 10.1203/00006450-197404000-00655
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exercise as a Screening Test for Uteroplacental Insufficiency (Upi)

Abstract: S t a t e Unlv., Hutzel osp. ~? l~p . % t~l i c h . , Dept. of Peds., D e t r o i t , Mich.H(Intr? by P.V.Woolley, J r . )A number of h o s p i t a l s s t i l l e x i s t w i t h t h e i r neonatal I C U n o t w i t h i n t h e v i c l n i t y of the d e l i v e r y rooms.Thismeans t r a n s p o r t i n compromised & u n s t a b l e i n f a n t s some d i s t a n c e t o reach t h e I~U . At Hutzel Hosp. t h i s problem was solved by t h e u s e of a NRRU i n t h e d e l i v e r y s u i t e . This r e p o r t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…The present results agree well with the reports by Hon and Wohlgemuth (14) and Stembera (27) which demonstrated no, or only slight, FHR changes after step-test in uncomplicated pregnancies. However, Pomerance et al (24) showed that in 9 per cent of normal pregnant women, a reduction in FHR of more than 16 beats per minute followed a bicycle ergometer test at a load level similar to ours. The present fiidings confirm the greater reactivity to various stimuli of FBM compared with FHR.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present results agree well with the reports by Hon and Wohlgemuth (14) and Stembera (27) which demonstrated no, or only slight, FHR changes after step-test in uncomplicated pregnancies. However, Pomerance et al (24) showed that in 9 per cent of normal pregnant women, a reduction in FHR of more than 16 beats per minute followed a bicycle ergometer test at a load level similar to ours. The present fiidings confirm the greater reactivity to various stimuli of FBM compared with FHR.…”
Section: Discussionsupporting
confidence: 84%
“…Our knowledge of whether maternal physical activity affects the human fetus in normal gestation is at present incomplete. Only few clinically normal pregnant women subjected to exercise tests have shown any changes in the fetal heart rate (14,16,24,26,27). It has been suggested that measurements of fetal breathing movements (FBM) in man provide a more sensitive indication of fetal physiological state than does fetal heart rate (FHR) (5).…”
mentioning
confidence: 99%
“…Another possible explanation involves the effect of intense physical activity on uteroplacental blood flow. Maternal exercise is known to reduce uteroplacental blood flow (23). The restriction of physical activity lowers blood pressure and promotes diuresis (19,24).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have not analyzed factors in this population size to assess those mother who are at risk of the development of an abnormal trace in labor. 15 This noninvasive assessment of fetal heart rate patterns also gives an indication of fetal heart rate response to moderate exercise. Previous investigators have looked at the effect of moderate exercise on the resistance to blood flow (systolic/diastolic) in the umbilical and uterine artery.…”
Section: Commentmentioning
confidence: 99%